Resolving the Binary Components of the Outbursting Protostar Hbc 494 with Alma - Perez-Marquez, S (Oxford University Press, 2023)
Episodic accretion is a low-mass pre-main sequence phenomenon characterized by sudden outbursts of enhanced accretion. These objects are classified into two: protostars with elevated levels of accretion that lasts for decades or more, called FUors, and protostars with shorter and repetitive bursts, called EXors. HBC 494 is a FUor object embedded in the Orion Molecular Cloud. Earlier Atacama Large (sub-)Millimeter Array (ALMA) continuum observations showed an asymmetry in the disc at 0 . 2 resolution. Here, we present follow-up observations at ∼0. 03, resolving the system into two components: HBC 494 N (primary) and HBC 494 S (secondary). No circumbinary disc was detected. Both discs are resolved with a projected separation of ∼0. 18 (75 au). Their projected dimensions are 84 ± 1.8 × 66.9 ± 1.5 mas for HBC 494 N and 64.6 ± 2.5 × 46.0 ± 1.9 mas for HBC 494 S. The discs are almost aligned and with similar inclinations. The observations show that the primary is ∼5 times brighter/more massive and ∼2 times bigger than the secondary. We notice that the northern component has a similar mass to the FUors, while the southern has to EXors. The HBC 494 discs show individual sizes that are smaller than single eruptive YSOs. In this work, we also report 12CO, 13CO, and C18O molecular line observations. At large scale, the 12CO emission shows bipolar outflows, while the 13CO and C18O maps show a rotating and infalling envelope around the system. At a smaller scale, the 12CO and 13CO moment zero maps show cavities within the continuum discs’ area, which may indicate continuum over-subtraction or slow-moving jets and chemical destruction along the line of sight. © 2023 The Author(s)